Developing an Internet‐Based Decision Aid for Women Choosing Between Vaginal Birth After Cesarean and Planned Repeat Cesarean. (8th June 2015) - Shorten, Allison; Fagerlin, Angela; Illuzzi, Jessica; Kennedy, Holly P.; Lakehomer, Hannah; Pettker, Christian M.; Saran, Allison; Witteman, Holly; Whittemore, Robin
<x xml:space="preserve">Abstract</x> Introduction In response to the call to develop strategies to engage women and providers in shared decision making, this article outlines a framework and process used to create an Internet‐based decision aid about birth choices after previous cesarean. Recognizing the potential benefits of mobile health information technology, a paper‐based decision aid was transformed into a secure, interactive Web site to meet the diverse needs of women and providers in this often challenging health care decision. Methods An iterative and participatory research approach was used, engaging targeted users (pregnant women and pregnancy care providers) in the design and development process. Results Women recommended that features and functions of the decision aid should include individualized information, trustworthy evidence, a secure and private site, quizzes to check knowledge, and a way to share values and preferences with their providers. Providers recommended individualized information for women, a process for women to share and document values and preferences with providers, and balanced, straightforward and complete information about the risks and benefits of each option. Discussion There is great potential for direct linkage between Internet‐based decision aids and the electronic medical record. Work is currently underway to integrate and evaluate the Internet‐based decision aid within busy practice settings to support shared decision making. This article is part of a special series of articles that address midwifery innovations in clinical practice, education, interprofessional collaboration, health policy, and global health.